A digitalização do trabalho dos motoristas de aplicativo no Brasil e no Chile: entre redes, plataformas e projetos. - Unda, Agustín Gabriel Rubilar (Universidade Federal de São Carlos, 2020)
The structural changes in the world economy and the current technological advances have fostered a new business model operated through digital platforms, giving rise to new forms of work organization in which data extraction and processing become new sources of raw material, giving shape and meaning to what many authors have been calling platform capitalism. This research aims to contribute to the understanding of this context, by exploring the potential impacts of this business model. While considering a complementary concept, that of a connectionist capitalism, the focus is on two of its main attributes: professional insertion via networks and flexible work. This research sought to explore the emerging theme of platform capitalism and its impacts on the work organization of drivers who use transport passenger applications in Brazil and Chile. To do this, the research employed both a theoretical approach through a systematic bibliographic review and narrative bibliographic research, as well as an empirical approach, (i) through a survey of 54 Brazilian drivers and 56 Chilean drivers, (ii) semi-structured interviews with 30 Brazilian drivers and 17 Chilean drivers; (iii) observant participation in 13 Facebook groups and two WhatsApp groups, one of them with 144 participants and the other with one 48. Among the results found it is highlighted that: (i) the bibliographic review of the literature on the subject provided the scope for systematization of the researched studies around three main axes: new work practices, job insecurity, and labor legislation, (ii) the empirical research revealed that despite the driver’s perceptions (from both countries) of exploitation, excessive poorly paid work hours, and high job insecurity. Yet, the flexibility is considered the great advantage of this process of professional insertion in a context of unemployment and increasingly precarious work.
La digitalización del trabajo de los conductores de aplicaciones en Brasil y en Chile: entre redes, plataformas y proyectos.
Keywords: Capitalismo de plataforma; Organização do trabalho; Precarização do trabalho; Motoristas de aplicativos no Brasil; Motoristas de aplicativos no Chile; Platform capitalism; Work organization; Precarious work; Application drivers in Brazil; Application drivers in Chile; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO